Antidiabetic and antioxidant effects of catalpol extracted from Rehmannia glutinosa (Di Huang) on rat diabetes induced by streptozotocin and high-fat, high-sugar feed. Issue 1 (December 2016) - Zhu, Huifeng; Wang, Yuan; Liu, Zhiqiang; Wang, Jinghuan; Wan, Dong; Feng, Shan; Yang, Xian; Wang, Tao
Abstract Background Diabetes, associated with hyperlipidemia and oxidative stress, would lead to an increased production of reactive oxygen species.Rehmannia glutinosa (Di Huang) is widely used to nourishyin, invigorate thekidney (shen ), and treatxiao ke (a diabetes-like syndrome in Chinese medicine). This study aims to investigate the antidiabetic and antioxidant effects of catalpol fromR. glutinosa on rat diabetes induced by streptozotocin (STZ) and high-fat, high-sugar feed. Methods Rats (eight rats in each group at least) were induced diabetes by an initial high-fat high-sugar feed for 3 weeks, followed by an intraperitoneal injection of STZ (30 mg/kg) for 3 days, and rats were fasted overnight before treatments. Catalpol at a dose of 0, 5, 10, 20 or 50 mg/kg was administrated through bolus intravenous injection to the experimental rats to find the most effective anti-hyperglycemic dose of catalpol to further study body weight loss, water intake, and food intake. The most effective catalpol dose was given to the diabetic model rats with hyperlipidemia, and the levels of blood sugar, plasma total cholesterol (TC), triglyceride (TG), and high-density lipoprotein cholesterol (HDL-C) were measured after catalpol administration once a day for 2 weeks. An oral glucose challenge test (OGCT) was performed after above experiments in which the most effective dose of catalpol has been determined. Levels of glutathione peroxidase (GSH-PX), catalase (CAT), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured by corresponding reagent kits and morphological changes of the pancreas were observed with histopathological examination using H&E stain. Results Catalpol at a dose of 50 mg/kg ameliorated body weight loss and increased water and food intake. Catalpol also attenuated the increase of plasma TC (P = 0.0067) and TG (P = 0.0084) and increased HDL-C (P = 0.0336). The OGCT revealed that catalpol reduced the increase of plasma glucose. The activities of antioxidative enzymes (SOD, P = 0.0037; GSH-PX, P = 0.0066; CAT, P = 0.005) were enhanced and MDA was reduced (P = 0.003). Furthermore, catalpol reduced the morphological impairment of the pancreas. Conclusion Catalpol protected against STZ-induced diabetes with high-fat and high-sugar feed with ameliorated structural impairment of the pancreas and restored balance between oxidative enzymes and antioxidative enzymes.